Developing a Toolkit for evaluation of gamification in educational environments - Lopes, Vinícius; Isotani, Seiji; Matos, Diego Dermeval Medeiros da Cunha (Anais Estendidos do Congresso Brasileiro de Informática na Educação (CBIE), 2023)
Gamification has been achieving good results in the improvement of motivation and engagement of students compared to traditional teaching methods. However, there is still no consensus regarding the metrics, instruments, and procedures for validating and evaluating the gamification design and effects in these contexts. In this paper, we report the development of a Toolkit to assist in the evaluation of gamification design in learning environments. We intend to provide, through this Toolkit, a group of empirically validated evaluation instruments categorized by their evaluation criteria, such as motivation, engagement, system usability and user experience, in order to provide the most effective evaluation solution for each gamification scenario.